Exploring Students’ Experiences in Learning Speaking through Total Physical Response Method - Hidayat, Akhmad Nuris; hidayat, akhmad (Mastery: Master of English Language Journal, 2025)
This study aims to explore students’ experiences in learning English speaking through the implementation of the Total Physical Response (TPR) method. Using a qualitative descriptive design, the research focuses on how students perceive, respond to, and engage with speaking activities that involve physical actions and commands. Data were collected through classroom observations, semi-structured interviews, and students’ reflective notes. The findings indicate that TPR creates a more interactive and enjoyable learning atmosphere, reduces students’ anxiety in speaking English, and helps them remember vocabulary and expressions more effectively. Students reported that the use of gestures and physical movement facilitated better comprehension and increased their willingness to participate in speaking tasks. However, some challenges were also identified, such as limited vocabulary coverage and the need for teacher creativity in designing varied activities. Overall, this study suggests that TPR can be an effective strategy to enhance students’ speaking ability and foster positive learning experiences in the English as a Foreign Language (EFL) classroom.